Music, asked by harsh33839271, 1 year ago

12. p(x) = x-ax+6x-a, g(x) = x-a.​

Answers

Answered by ItzDangerBhai
0

{ \underline{ \underline{\boxed{ \green{ \bold {\:Given}}}}}}\: \red \downarrow

{ \tt{p(x) \:  =  \: x -  ax + 6x   -   a}}  \\{ \tt{g(x) \:  =  \: x - a}}

{ \underline{ \underline{\boxed{ \green{ \bold {Solution}}}}}}\: \red \downarrow

{ \tt{g(x) \:  =  \: x - a}} \\{ \tt x  - a   \: =  \: 0} \\{ \tt x \:  =  \: 0 \:  +  \: a }\\ { \tt x \:  = a}

{ \tt {\rightarrow{p(x) \:  =  \: x -  ax + 6x   -   a}}}  \\

{ \tt {\rightarrow{p(a) \:  =  \: (a) -  a(a)+ 6(a)   -   a}}} \\ { \tt{ \:  =  \: \cancel a \:  - 2a \:  +  \: 6a \:  - \cancel a}} \\ { \tt{ \: p(a) \:  =  \:   4a   \:  \leftarrow{\orange {(ans)}}}}

Similar questions